Soldiers : Great Stories of War & Peace - Hastings, Max (London William Collins, 2021)
'A gripping new collection from Max Hastings that puts you at the heart of the battle ... Compelling' Daily Mail 'An unmissable read' Sunday Times
Include Color Illustrations and Index
Keywords: Military history